CONVERSÃO AO ISLÃ: UMA ANÁLISE SOCIOLÓGICA DA ASSIMILAÇÃO DO ETHOS RELIGIOSO NA SOCIEDADE MUÇULMANA SUNITA EM SÃO BERNARDO DO CAMPO NA REGIÃO DO GRANDE ABC - RAMOS, VLADEMIR LÚCIO (2003)
This dissertation has the purpose to analyze the religious phenomenon of conversion to Islam. Based in a practical experience the conversion to Islam is analyzed as a process of assimilation of the religions ethos undertook by Brazilian without Arabian origins. In a sociological purpose the concept of conversion was widen and articulated among concepts of identity and assimilation. The converts interviewed are integrated to a sunite muslin society at São Bernardo do Campo in the area of the Grande ABC, São Paulo, organized around a Latin American Islam Publishing Center (Centro de Divulgação do Islã para a América Latina – CDIAL) and a mosque named Abu Bakr Assedic. This dissertation attempts to comprehend the earlier social and religious reasons for conversion and its consequences. It is also kept up that the process of conversion is gradual and undertook by an active person who examines its own experiences can build an unique identity which differs the Arabian ethos.